Crimen y castigo en 'La contienda entre Horus y Seth' - (:unkn) unknown (Universidad de Buenos Aires. Facultad de Filosofía y Letras. Instituto de Historia Antigua Oriental "Dr. Abraham Rosenvasser", 2006)
In Ancient Egypt, the coexistence of kinship and State logics of social organization can be seen not only in the context of social practices but also in the divine world, were gods usually appear exerting kinship and State-like procedures. Here we will focus on the tale of The Contendings of Horus and Seth, contained in the Papyrus Chester Beatty I, in which these two gods litigate for the right to the office of Osiris before a divine court. At first sight, the judicial practices involved in the tale might appear as representatives of State judicial procedures. However, several events which take place during the trial tend to offer an image very different from those representations coming from the realm of State judicial courts, and suggest a scenario comparable to the ways of solving conflicts in non-State societies, organized through kinship practices. We will consider four episodes of The Contendings, in which four different gods - namely, Baba, Anty, Horus and Seth - are regarded as deservers of some kind of punishment. We will suggest that the remarkable differences in the resolutions of these episodes can be connected with the diverse influence kinship and State principles exert throughout the tale.
Estudios sobre parentesco y Estado en el Antiguo Egipto
43 ref.
Keywords: Historia egipcia; Historia antigua; historia social; antropología; parentesco; familia; delitos; castigo; Estado; Egipto